PERANCANGAN VISUAL BUKU ILUSTRASI SEBAGAI MEDIA PENGENALAN TARIAN NUSANTARA UNTUK ANAK-ANAK SD OLEH SANGGAR TARI SVADARA - Dewangga, Shadiq; Cempaka, Gilang (INSIDE : Jurnal Desain Interior, 2025)
Design of the illustration book “Taripedia” is a media for introduction traditional archipelago dances for elementary school children initiated by Svadara Dance Studio, South Jakarta. Traditional archipelago dances that contain noble values of the Indonesian nation need to be introduced early so that the younger generation can appreciate and preserve the cultural heritage of the archipelago. This illustration book is designed with attractive illustrations in accordance with the characteristics of children, such as the use of colorful images, simple sentences, and easy-to-understand information. The design of the illustration book “Taripedia” contains general information about the variety of traditional dances of the archipelago spread across all provincial representatives in Indonesia. This book will be released in conjunction with the evaluation event or year-end exam for Svadara Dance Studio students, named “Ekliptika”. The final result of this research is an illustration book that not only functions as a learning medium, but also as a means of fun entertainment for elementary school-age children. The book design method uses descriptive qualitative research methods through literature review, interviews, and observations. It is expected that this illustration book can be an effective medium in introducing and fostering a love for traditional archipelago dances in elementary school-age children.